A review on the effect of micro- and nano-plastics pollution on the emergence of antimicrobial resistance. (January 2023) - Gaur, Vivek Kumar; Sirohi, Ranjna; Bhat, Mohd Ishfaq; Gautam, Krishna; Sharma, Poonam; Srivastava, Janmejai Kumar; Pandey, Ashok
Abstract: The recent upsurge in the studies on micro/nano plastics and antimicrobial resistance genes has proven their deleterious effects on the environmental and human health. Till-date, there is a scarcity of studies on the interactions of these two factors and their combined influence. The interaction of microplastics has led to the formation of new plastics namely plastiglomerates, pyroplastics. and anthropoquinas. It has long been ignored that the occurrence of microplastics has become a breeding ground for the emergence of antimicrobial resistance genes. Evidently microplastics are also associated with the occurrence of other pollutants such as polyaromatic hydrocarbons and pesticides. The increased use of antibiotics (after Covid breakout) has further elevated the detrimental effects on human health. Therefore, this study highlights the relation of microplastics with antibiotic resistance generation. The factors such as uncontrolled use of antibiotics and negligent plastic consumption has been evaluated. Furthermore, the future research prospective was provided that can be helpful in correctly identifying the seriousness of the environmental occurrence of these pollutants. Graphical abstract: Image 1 Highlights: Microplastics and antimicrobial resistance has become a global menace. Microplastics serve as breeding ground for AMR microorganisms. They also interact with other persistent pollutant in the environment. Combating strategies should be focused considering both the pollutants together.